THE EFFECTIVENESS OF PAIN PREVENTION EDUCATION ON INCREASING RUNNERS’ KNOWLEDGE AT JAYABAYA SPORTSHALL, KEDIRI CITY: EFEKTIVITAS EDUKASI PENCEGAHAN NYERI TERHADAP PENINGKATAN PENGETAHUAN PELARI DI GOR JAYABAYA, KOTA KEDIRI - Aldino Faizul Wafa, Aldino; Aldino Faizul Wafa; Herdyansyah Akdhiat Syafurryzal; Mattew Jopan Bintatar Simanjutak; Arshy Prodyanatasari (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
Jogging is a popular sport with broad health benefits, but it can lead to musculoskeletal complaints ifperformed without a proper understanding of technique and injury-prevention principles. A goodunderstanding of running technique, warm-up, and mild pain management is necessary to keep jogging safe and sustainable. This study aims to analyze the effectiveness of pain-prevention education in improving runners’ knowledge and attitudes in the GOR Jayabaya community, Kediri City. The activity was carried out using a Participatory Action Research (PAR) approach, involving 7 participants: 6 women and 1 man. The research instrument was a four-point Likert-scale questionnaire covering safe jogging techniques, pain prevention, warm-up, cool-down, and mild pain management. Data were analyzed using quantitative descriptive methods to characterize participants’ understanding levels after the education. The results showed that the participants’ average overall score was 30.00, with a range of 27–33 and a standard deviation of 2.309, indicating a high level of knowledge improvement. These findings confirm that community-based participatory education is effective in increasing runners’ awareness and understanding of safe jogging practices and injury-prevention strategies.